PENINGKATAN KESEHATAN JIWA MELALUI PERAN KADER MENUJU KELURAHAN SIAGA SEHAT JIWA - Sambodo Sriadi Pinilih; Estrin Handayani; Elza Shelviana; Evi Rositasari; Maulana Aziz (STMIK Royal, 2020)
Abstract: The problem of disability is now a global health problem. As a result of disability, problems affect the productivity and quality of health of individuals and the community. Persons with disabilities are not just people who have physical disabilities. People with mental disorders (ODGJ) are included in a group of people with disabilities. The stigma of Indonesian society that is still very strong regarding ODGJ is not as strong as that of other people with disabilities. This should not be allowed because it will result in a violation of dignity and value. The purpose of this activity is to establish and optimize the role of Mental Health Cadres (KKJ) in the community who are trained in the early detection of mental disorders in the community. This activity was carried out in the Magelang village in the Central Magelang subdistrict, Magelang city. With a population of 6,441 people, most of the community work in the Magelang village is working in the field of community services, government & individuals. In the 2019 Magelang sub-district has 18 patients with mental disorders. The results of the activities of the formation of mental health cadres (KKJ) in the community trained as many as 15 active cadres and are able to conduct early detection of mental disorders in the community so that the number of ODGJ of Magelang village is known to be 34 people and there are 2 people at risk of mental disorders. After knowing the number of ODGJ cadres implementing to the community one of them by providing psychological knowledge for families and communities.Keywords: disability; mental health cadres; mental disorders Abstrak: Masalah disabilitas saat ini menjadi masalah kesehatan global. Akibat adanya masalah disabilitas mempengaruhi produktivitas dan kualitas kesehatan perseorangan maupun masyarakat. Penyandang disabilitas bukan hanya orang yang mengalami kecacatan fisik saja. Orang dengan gangguan jiwa (ODGJ) termasuk dalam golongan penyandang disabilitas. Stigma masyarakat Indonesia yang masih sangat kuat mengenai ODGJ tidak sekuat pada penyandang disabilitas lainnya. Hal ini tidak boleh dibiarkan karena akan mengakibatkan pelanggaran martabat dan nilai. Tujuan dari kegiatan ini untuk membentuk dan mengoptimalkan peran Kader Kesehatan Jiwa (KKJ) di masyarakat yang terlatih dalam melakukan deteksi dini kasus gangguan jiwa di masyarakat. kegiatan ini dilakukan dengan metode pendampingan kepada kader serta membantu para kader yang telah melakukan pelatihan tentang kesehatan jiwa. Dalam melakukan deteksi dini gangguan jiwa dimasyarakat dan pemetaan rumah penyandang disabilitas. Hasil kegiatan terbentuknya Kader Kesehatan Jiwa (KKJ) di masyarakat yang terlatih sebanyak 15 kader aktif dan mampu melakukan deteksi dini gangguan jiwa dimasyarakat sehingga diketahui jumlah ODGJ kelurahan magelang sebanyak 34 orang dan resiko gangguan jiwa ada 2 orang. Setelah diketahuinya jumlah ODGJ kader melakukan implementasi ke masyarakat salah satunya dengan cara memberikan pengetahuan psikologis bagi keluarga dan masyarakat.Kata Kunci: disabilitas; gangguan jiwa; kader kesehatan jiwa